Nursing Students' Motivation, Awareness, and Knowledge of Women's Health: A Norwegian Quasi-Experimental Study - Christine Tørris (MDPI AG, 2024)
Background: The knowledge of sex and gender differences in disease are crucial for nursing students. Methods: This quasi-experimental study assesses nursing students' motivation, awareness, and knowledge related to women's health before and after a pathology course for first-year nursing students, using a pre-posttest design (pretest: n = 312, posttest: n = 156). Results: More than 90% of students were motivated to learn about sex and gender differences in pathology. Awareness increased significantly for the following topics: cardiovascular disease (CVD), osteoporosis, and breast cancer (BC). The knowledge level was low for CVD and high for BC, where the knowledge level increased significantly for BC. Having another first language predicted CVD (B −2.123, 95% CI −3.21 to −1.03) and osteoporosis (B −0.684, 95% CI −0.98 to −0.39) knowledge negatively, while age group (≥21 years) predicted menstruation (B 0.179, 95% CI 0.03 to 0.33) and BC (B 0.591, 95% CI 0.19 to 1.00) knowledge positively, in the total sample (pre- and postdata, n = 468). Conclusion: There is a lack of pathology knowledge among nursing students, especially related to CVD and symptoms of heart attacks in women. To ensure equality in health for women, these perspectives should be systematically integrated into the nursing students' curriculum in the future.